2022
DOI: 10.1002/jcu.23388
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial work—A new tool for early detection of rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone chemotherapy induced‐cardiotoxicity in hematological patients

Abstract: Background Rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone (RCHOP) chemotherapy in non‐Hodgkin's lymphoma (NHL) has risk of cardiotoxicity. Purpose To determine the role of myocardial work and biomarkers in subclinical diagnosis and prediction of cardiotoxicity. Methods The 130 NHL patients (52 ± 9 years, 62% men) scheduled for RCHOP, with LVEF>50%, were evaluated at baseline, after third cycle and chemotherapy completion for 3D LVEF, 2D myocardial deformation (longitudinal, radial, circumfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…19,[40][41][42] Assessments of MW were already done in preclinical and adult cohorts patients. 21,22,43 For example, MW has been assessed in ischemic cardiac disease, allowing the detection of subclinical coronary artery disease without any regional wall motion abnormalities, and has more sensitivity for myocardial oxygen consumption. 26 In pediatric population, Zhan et al recently demonstrated that global MWI enhanced hypertensive heart disease evaluation and cardiac dysfunction during and after chemotherapy follow-up.…”
Section: Lower Mw In Cls Especially On Apical Segmentsmentioning
confidence: 99%
“…19,[40][41][42] Assessments of MW were already done in preclinical and adult cohorts patients. 21,22,43 For example, MW has been assessed in ischemic cardiac disease, allowing the detection of subclinical coronary artery disease without any regional wall motion abnormalities, and has more sensitivity for myocardial oxygen consumption. 26 In pediatric population, Zhan et al recently demonstrated that global MWI enhanced hypertensive heart disease evaluation and cardiac dysfunction during and after chemotherapy follow-up.…”
Section: Lower Mw In Cls Especially On Apical Segmentsmentioning
confidence: 99%
“…In these patients, MW seems to diagnose subclinical cardiotoxicity and predict left ventricular (LV) systolic decline. An early reduction of global work efficiency with more than 5%, after third cycle of chemotherapy, seems to predict the occurrence of cardiotoxicity, after the ending of cures 2 . The manuscript is very important, first, because the authors used, for the first time MW in the RCHOP chemotherapy‐induced myocardial dysfunction detection.…”
Section: Figurementioning
confidence: 99%
“…In the article entitled: “Myocardial work – A new tool for early detection of RCHOP chemotherapy induced‐cardiotoxicity in hematological patients” by Mihalcea et al, 2 the authors aimed “to determine the role of myocardial work (MW) and biomarkers in subclinical diagnosis and prediction of cardiotoxicity” in patients non‐Hodgkin's lymphoma. In these patients, MW seems to diagnose subclinical cardiotoxicity and predict left ventricular (LV) systolic decline.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations